2022
DOI: 10.3389/fonc.2022.881641
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer Properties of Curcumin Against Colorectal Cancer: A Review

Abstract: Colorectal cancer (CRC) is one of the most common and reoccurring diseases, as well as the world’s second largest cause of mortality. Despite existing preventative, diagnostic, and treatment methods, such as chemotherapy, the number of instances rises year after year. As a result, new effective medications targeting specific checkpoints should be developed to combat CRC. Natural compounds, such as curcumin, have shown significant anti-colorectal cancer characteristics among medications that can be used to trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
50
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 68 publications
0
50
0
1
Order By: Relevance
“…Similarly, Cur exerts several antitumor properties against CRC acting through a variety of cellular signaling pathways [17]. First, Cur could interrupt the cell cycle and accelerate cell death, and this effect can assist in inhibition of the metastatic ability of CRC cells [11]. Second, the anticancer potential of Cur on CRC can be mediated by activating the cell death pathway [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Cur exerts several antitumor properties against CRC acting through a variety of cellular signaling pathways [17]. First, Cur could interrupt the cell cycle and accelerate cell death, and this effect can assist in inhibition of the metastatic ability of CRC cells [11]. Second, the anticancer potential of Cur on CRC can be mediated by activating the cell death pathway [11].…”
Section: Discussionmentioning
confidence: 99%
“…Third, Cur can reduce chemoresistant cancer cells by acting on the population of CRC stem cells [11]. Finally, Cur can regulate gut ora, thus in uencing CRC progression [11]. A randomized controlled trial reported that supplementation with 500 mg curcuminoids/day for 8 weeks can improve the functional scales and global quality of life compared to placebo in patients with stage 3 CRC [30].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin (CUR)-an active polyphenol extracted from the dried rhizomes of Curcuma longa-has been traditionally used for dietary and medical purposes worldwide (Li KX. et al, 2022;Jin et al, 2022;Ojo et al, 2022). CUR shows a wide range of pharmacological activities, including anti-inflammatory and antioxidant activities, in various disease models (Yang et al, 2020;Uddin et al, 2021;Fan and Lei, 2022).…”
Section: Curcuminmentioning
confidence: 99%
“…Curcumin (CUR) is known for its therapeutic properties; among these, antioxidant, anti-inflammatory and anti-cancer ones stand out [ 1 , 2 ]. Unfortunately, curcumin is poorly water-soluble and bioavailable [ 3 ]; these are the drawbacks that hamper its great therapeutic properties and hold back its use in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%